Rasionalitas dalam swamedikasi vitamin c pada masa pandemi covid - 19 di kota denpasar: Rationality in self-medication of vitamin c during the covid-19 pandemic in denpasar city - Suryaningsih, Ni Putu Aryati; Reganata, Gde Palguna; Sutema, Ida Ayu Manik Partha; Putri, Dhiancinantyan Windydaca Brata (Bali Medika Jurnal, 2021)
Background The pandemic we can call Coronavirus Disease (COVID-19) has a significant impact in all sectors of human life.Indonesia reported its first cases of COVID-19 on March 2,2020 totalin two cases (WHO, 2020). World Health Organization (WHO) recommends to consumption healthy foods and increase immunity with more vitamin that during the pandemic COVID-19.Vitamin C is an alternative to boost the immune system. Increasing consumption of vitamin C needs to be seen by the rationality of using self-medicated vitamin C during the COVID-19 pandemic. Inappropriate or excessive use of vitamins can result in damage to organs such as the kidneys. The purpose of this study was to describe the rationality of Samedication vitamin C during the pandemic COVID-19 in the Denpasar City. Methods: The design of this study is descriptive using a descriptive design that uses non-probability sampling t. The instrument used is a questionnaire. The sample population is 100 respondents in the community in Denpasar. Results: The results of the study show the rationality of using swamedication vitamin C during the pandemic COVID- 19 in Denpasar amounting to 84.73% rational and irrationally of 15.27%, the rationality were measured from the right indication of  the drug, the right way of administration. medication, proper dosage, proper storage and side effect alert.